2016
DOI: 10.17816/rcf14324-33
|View full text |Cite
|
Sign up to set email alerts
|

About the influence of metal oxide nanoparticles on living organisms physiology

Abstract: Recently the number of materials and goods produced by nanotechnology has been growing rapidly, leading to an increased penetration of nanoparticles into biosystems. To assess the risks associated with the production and circulation of nanoproducts should be developed methods for the rapid diagnostics of nanopathology. In this work, it has been experimentally shown that the introduction of metal oxides nanoparticles (TiO2, ZnO, Al2O3, CeO2) to laboratory mice leads to changes some profiles of specific hematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition, the efficiency of titanium compounds during the process of organic compound removal, namely a decrease in the COD index, was, on average, 5-7% higher, which should have a positive effect on further biological treatment. In addition, it should be noted that when the titanium salts are used as the coagulants, the final treatment products will be titanium dioxide that has a much lower toxicity compared to the aluminum compounds [27].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the efficiency of titanium compounds during the process of organic compound removal, namely a decrease in the COD index, was, on average, 5-7% higher, which should have a positive effect on further biological treatment. In addition, it should be noted that when the titanium salts are used as the coagulants, the final treatment products will be titanium dioxide that has a much lower toxicity compared to the aluminum compounds [27].…”
Section: Resultsmentioning
confidence: 99%
“…Nano-sized copper oxide (nano-CuO) is a widespread metal-containing nanomaterial; it is used in various production spheres as a component in sensors (49 %), catalysts (20 %), surfactants (6 %), anti-microbial substances (4 %), specific dyes (21 %), and other products [3][4][5][6][7][8]. The research work [9] revealed that copper oxide nanoparticles penetrated a human body predominantly via inhalation or oral introduction (with drinking water).…”
mentioning
confidence: 99%